ASSESSMENT OF SUBCLINICAL TARGET ORGAN DAMAGE BY COMPONENTS OF BLOOD PRESSURE: COMPARISON OF CENTRAL AND PERIPHERAL ARTERIAL PRESSURE. (June 2018) - Zuo, J.; Chu, S.; Tan, I.; Butlin, M.; Zhao, J.; Avolio, A.
Abstract : Objective: Central aortic pressure (cAP) has stronger association with markers of vascular function and compared to peripheral arterial pressure (pAP), particularly in groups with elevated cardiovascular risk. However, the potential clinical use of blood pressure (BP) components of cAP and pAP as markers of target organ damage (TOD) has not been well established. The Aim of this study was to assess the association of pulsatile components of cAP and pAP with markers of TOD and to seek any differences related to age. Design and method: From noninvasive waveform recordings, indices of cAP and pAP (pulse pressure [aPP, pPP, augmentation index. AIx) were assessed in relation with TOD in 770 hospital inpatients (age 60.0 ± 10.0 years, 473 males) with primary hypertension (brachial BP > 1409/90 mmHg). TOD was quantified by arterial stiffness (carotid-femoral pulse wave velocity [cfPWV]), carotid intima-media thickness (IMT), urine albumin-to-creatinine ratio (ACR). Subclinical TOD was defined as carotid IMT > 0.9 mm, urine ACR > 3.5 mg/mmol (females) and > 2.5 mg/mmol (males) and/or cfPWV > 12 m/s. Results: Females showed greater cPP (mmHg) (50 ± 13) compared to males (40 ± 13) (p < 0.01) for similar pPP (mmHg) (62 ± 15, 60 ± 16 respectively). For the whole cohort, cPP and pPP were correlated with cfPWV (r = 0.41 vs. r = 0.40; p < 0.01), ACR (r = 0.24 vs. r = 0.27; p < 0.01) and carotid IMT (r = 0.14 vs. r = 0.15; p < 0.01). Each SD increase in pPP and cPP was associated with respective Odds Ratios (of 2.7, 2.9 (cfPWV), 1.2, 1.4 (ACR), 1.46, 1.53 (IMT). For males > 60 years, each SD increase in AIx corrected for heart rate was associated with 1.5 times increase in risk of cfPWV >12 m/s. When corrected for confounding variables, cPP had higher predictive power for TOD for age >60 years compared to pPP. Conclusions: Both pPP and cPP were associated with TOD in a hypertensive population. However, compared to pPP, cPP provides independent and additional information associated with TOD elderly hypertensive subjects (> 60 years). Additional hemodynamic indices of cAP as potential biomarkers of subclinical TOD require validation by further prospective studies.